Hyaluronic Acid Nanoparticles as a Topical Agent for Treating Psoriasis - Lee, Wang Hee; Rho, Jun Gi; Yang, Yeyoung; Lee, Seulbi; Kweon, Sohui; Kim, Hyung Mo; Yoon, Juhwan; Choi, Hongseo; Lee, Eunyoung; Kim, Su Ha; You, Sohee; Song, Yujin; et al. (ACS Nano, 2022)
Although conventional topical approaches for treating psoriasis have been offered as an alternative, there are still unmet medical needs such as low skin-penetrating efficacy and off-target adverse effects. A hyaluronic acid nanoparticle (HA-NP) formed by self-assembly of HA-hydrophobic moiety conjugates has been broadly studied as a nanocarrier for long-term and target-specific delivery of drugs, owing to their excellent physicochemical and biological characteristics. Here, we identify HA-NPs as topical therapeutics for treating psoriasis using in vivo skin penetration studies and psoriasis animal models. Transcutaneously administered HA-NPs were found to be accumulated and associated with pro-inflammatory macrophages in the inflamed dermis of a psoriasis mouse model. Importantly, HA-NP exerted potent therapeutic efficacy against psoriasis-like skin dermatitis in a size-dependent manner by suppressing innate immune responses and restoring skin barrier function without overt toxicity signs. The therapeutic efficacy of HA-NPs on psoriasis-like skin dermatitis was due to the outermost hydrophilic HA shell layer of HA-NPs, independent of the molecular weight of HA and hydrophobic moiety, and comparable with that of other conventional psoriasis therapeutics widely used in the clinical settings. Overall, HA-NPs have the potential as a topical nanomedicine for treating psoriasis effectively and safely.
Keywords: Adverse effect; Hydrophobic moieties; Medical needs; Nanocarriers; Psoriasi; Self assembled nanoparticles; Skin barrier functions; Skin inflammation; Therapeutic efficacy; Topical therapeutic; Animals; Dermatitis; Hyaluronic Acid; Mice; Nanoparticles; Psoriasis; Skin; hyaluronic acid; psoriasis; self-assembled nanoparticle; skin barrier function; skin inflammation; topical therapeutics